Pola Komunikasi Komunitas Rumah Belajar Sahaja Bandung (Studi Etnografi Komunikasi Tentang Pola Komunikasi Antara Pengajar dan Anak Jalanan di Rumah Belajar Sahaja Bandung) - Dwi Rizqi Anta; Arie Prasetio (Communicare : Journal of Communication Studies, 2017)
Education is the right of every Indonesian child. No exception a street child who are spend most of the time on the road. One of community that works in education especially for street child is Rumah Belajar Sahaja’s in Bandung community. Rumah Belajar Sahaja’s community is a place for street child to get education through teaches and learn activities. In every teach and learn activity there is a pattern of communication by teachers and street child. The purpose of this study is to form a new communication pattern between teachers and street child to attract children's learning interests. The formed communication pattern is expected to be applied in the Rumah Belajar Sahaja’s community so as to attract more street children to learn. The theory review used in this research is communication, interpersonal communication, communication process, communication ethnography, and communication pattern. This research uses ethnography method of communication based on constructivist paradigm. The results showed that the process of communication, communication components and relationships between communication components to form communication patterns of Rumah Belajar Sahaja’s community. Teachers approach with street child, street child follow the rules of Rumah Belajar Sahaja’s community, the teacher uses coercive communication. Food and beverages are distributed to street child who are implementing the rules of Rumah Belajar Sahaja Bandung